Analysis of Human-Building Interactions in Office Environments: to What Extent Energy Saving Boundaries can be Displaced? - Zaidan, Esmat; Ghofrani, Ali; Dokaj, Ernest (Frontiers in Energy Research, 2021)
Building energy consumption can be enhanced to a certain level, but human-oriented dimensions can open the doors to new opportunities. This article presents an assessment on the interactions between human-driven factors and energy consumption patterns in office buildings based on empirical evidence and a co-simulation. The objective of this work is to evaluate a range for saving capacities as a result of readjusting occupants’ prior habits and engaging them in building operation by determining internal and external factors associated with human-building drivers, needs, actions, and systems. The study is based on a real office building, and according to real behavioral data and subjective measurement to analyze human attitudes and interactions with the building end-uses such as cooling, lighting, and equipment along with factors that directly impact energy use such as fenestrations and window blinds. The survey results are extensively investigated and the correlations between demographic/socioeconomic traits and behavioral factors are examined. The survey results are incorporated into a co-simulation testbed to represent occupant attitudes and behaviors and model human-building interactions accordingly. Different scenarios are designed to perform an assessment on the role of human factors such as attitude, awareness of consequences, habits, ascription of responsibility and personal/social norms on building energy end-uses. The outcomes of this study demonstrate that by adjusting behavioral factors in an office building, an energy saving between 9 and 18% can be achieved without sophisticated technology interface or building retrofit/upgrade. The results are elaborated, and recommendations are explained in detail.